Entwicklung und Herstellung naturähnlich verzweigter Kühlkörper für LED-Systeme - Herbold, Christian (Spektrum der Lichttechnik / Karlsruher Institut für Technologie (KIT), Lichttechnisches Institut, 2017)
In terms of general lighting applications, this work deals with the use of natural models for the heat dissipation of LEDs, their implementation into a complete LED system and ultimately its manufacturing. The result is a lighting system that represents a high technical performance in conjunction with a high aesthetic value that can be an example for the development of different LED systems.